Insulin Resistance Modulation with Lifestyle Modification- Proof-of-Concept Study in Rats - Asif, Afzal Haq; Nanjundan, Prem Kumar; Basavarajappa, Girish Meravanige; Sreeharsha, Nagaraja; Chandur, Uma; Roopashree, Teeka Srinivasasetty (Indian Journal of Pharmaceutical Education and Research, 2020)
Purpose: Fatigue, a physical and/or mental exhaustion is a common symptom of diabetes. Easy fatigability is not limited to uncontrolled diabetes however is comorbid with psychological, medical, metabolic, and chronic complications like insulin-resistance, glucose intolerance, and obesity. Methods: We analyzed the effect of lifestyle modification involving physical exercise and intake of omega 3 fatty acid-rich fish oil on insulin resistance and diabetic fatigue. For the same, diabetes was induced using single dose streptozocin injection in rats fed with a high-fat diet and were treated with fish oil alone and in combination with exercise training. Blood glucose levels, glucose tolerance, lipid profile, insulin levels, oxidative stress and glycogen content were monitored in rats exposed to swimming exercise and fatigue test. Results: Alone fish oil could improve symptoms of diabetic complications; however, the combination intervention of exercise and oral administration of fish oil significantly lowered the fasting blood glucose level and fatty acid profile in diabetic rats. Improvement in antioxidant profile was observed from the decreased levels of lipid peroxidation products and increased levels of antioxidants like superoxide dismutase and glutathione. Effective glucose disposal correlated with better insulin tolerance and improvement in lipid profile as indicated by a significant reduction in LDL, VLDL, free fatty acids, and leptin with an increase in HDL levels. Exercise-induced changes in the liver and skeletal tissue, enabling diabetic rats to restore their glycogen stores thus building the endurance required for prolonged exercise. Conclusion: Lifestyle modification with moderate exercise and consumption of antioxidant-rich fish oil is a novel and easy therapeutic intervention in the treatment of multifactorial syndrome of fatigue observed as a diabetic complication.
Keywords: Insulin; Fatigue; Diabetes; Fish Oil; Exercise